Steganography content detection by means of feedforward neural network. (1st January 2013) - Oplatková, Zuzana Komínková; Hološka, Jiří; Šenkeřík, Roman
This paper describes the technique for revealing of steganography content in images by means of feedforward neural network. The work is connected with cryptography for information encoding and additional method for information hiding, which is called steganography. The substance of the paper explains the principle of hidden information detection in images like JPEG format by means of feedforward neural network. The results show successful detection of four stego techniques by means of artificial neural network with one hidden layer.